What is Defined as Good in Company Codes of Ethics? - Ślęczek-Czakon, Danuta; Czakon, Tomasz (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
The paper concentrates on the problem of company codes of ethics. We want to present how the authors define what is desirable for company and stakeholders. From our point of view, company codes of ethics contain different axiological preferences. Our aim is to focus on these aspects of codes which are related with problems such as: way of creation code of ethics, perceived role of code of ethics, attitude towards main stakeholders. Our analysis will show how companies defines what is good in their activity (and what is good in general). Evaluation their ethicality will be based on comparison of contents company codes of ethics (demands, liabilities) with requirements of the business ethicists.